Volume Dan Frekuensi Transaksi Terhadap Harga Saham - Bambang Susanto; Sukadwilinda Sukadwilinda (Jurnal Ekonomi Manajemen Perbankan, 2022)
The study of the capital market, both fundamentally and technically, has produced many new findings (novelty) in theory, models and others. In this study, researchers tried to see the impact or market reaction when buying and selling by investors in the secondary market was marked by the variables transaction volume and transaction frequency whether it had an effect on stock prices. The results of the study with the LQ45 index sample and by using panel data show that the estimation test is a common effect in interpreting panel data regression. Hypothesis testing both partial and simultaneous obtained the results that there is a significant influence between the independent variables on the dependent variable. While the determination test obtained 95.69% of the independent variables affect the dependent variable and the rest are influenced by other variables.Â